2011
DOI: 10.1371/journal.pntd.0001396
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship between Urogenital Schistosomiasis and HIV Infection

Abstract: BackgroundUrogenital schistosomiasis, caused by infection with Schistosoma haematobium, is widespread and causes substantial morbidity on the African continent. The infection has been suggested as an unrecognized risk factor for incident HIV infection. Current guidelines recommend preventive chemotherapy, using praziquantel as a public health tool, to avert morbidity due to schistosomiasis. In individuals of reproductive age, urogenital schistosomiasis remains highly prevalent and, likely, underdiagnosed. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
178
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(182 citation statements)
references
References 55 publications
2
178
0
2
Order By: Relevance
“…26 These findings and ours support the hypothesis that men with urogenital schistosomiasis may more easily transmit HIV to their sexual partners due to tissue inflammation and bleeding, leading to higher concentrations of HIV in the semen of HIVschistosome coinfected men than in HIV-infected men without schistosome infection. 26,27 A recent prospective study demonstrated that men and women with the helminthic infection lymphatic filariasis had a 2-fold increased risk of incident HIV infection compared with those without filariasis. 28 Unlike schistosomiasis, filariasis is not known to have direct effects on the genital tract, suggesting that systemic immune changes induced by filariasis could increase HIV susceptibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 These findings and ours support the hypothesis that men with urogenital schistosomiasis may more easily transmit HIV to their sexual partners due to tissue inflammation and bleeding, leading to higher concentrations of HIV in the semen of HIVschistosome coinfected men than in HIV-infected men without schistosome infection. 26,27 A recent prospective study demonstrated that men and women with the helminthic infection lymphatic filariasis had a 2-fold increased risk of incident HIV infection compared with those without filariasis. 28 Unlike schistosomiasis, filariasis is not known to have direct effects on the genital tract, suggesting that systemic immune changes induced by filariasis could increase HIV susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…To participate in the study, men were asked to provide written informed consent or place their mark on the consent form. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. Nearly half of the men (328, 48.7%) had had more than one sexual partner in the past 6 months, and the majority of men reported that their sexual partners were typically more than 5 years younger.…”
Section: Methodsmentioning
confidence: 99%
“…The question of whether or not genital schistosomiasis might act as a co-factor has also been raised. 4 A few cases have been reported and published. 5,9 However, there is no convincing evidence that schistosomiasis can independently have a carcinogenetic effect without HPV.…”
Section: 4mentioning
confidence: 99%
“…3 Furthermore, schistosomiasis may increase the risk of human immunodeficiency virus (HIV) infection. 4 It has also been postulated that schistosomiasis may be a risk factor for the development of cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…1 Over 800 million people are at the risk of acquiring schistosomiasis in 76 endemic countries, with 46 of these countries in Africa. 2,3 Approximately 207 million people worldwide are infected with schistosomiasis 4 and 85% of the estimated number of infections are in the less developed areas of sub-Saharan Africa. Worldwide, Schistosoma haematobium causes more than half of the schistosomiasis infections, that is, approximately 112 million infections.…”
Section: Introductionmentioning
confidence: 99%